KONSEP DAN APLIKASI SIMULATOR TANUR PUTAR[The Concept and Application of Rotary Kiln Simulator] - Binudi, Rahardjo (Jurnal Metalurgi, 2012)
The sampling of the material to know it condition at any position along of the rotary kiln during operation is difficult to carry out. To overcome the concept for using such like small size (laboratory scale) which basis on mass and energy transport phenomena have been developed.. The concept of the use of rotary kiln simulator on the smaller size (laboratory experiments) are expected to observe the event as the actual rotary kiln operation. Observation of high temperature heating process results against such material, the level of reduction, metallized, metallized shapes and sizes, types of slag caused by changing parameters such as rotation speed, rate of incoming material, operating temperature, the rate of gas heaters can be studied more accurately and more easily . This simulator consists of three main components, namely combustion components, component heaters, and stack components and equipped with a feeder of raw materials and expenses sample, instrumentation and control equipment.